Serotonergic and dopaminergic mechanisms in graft-induced dyskinesia in a rat model of Parkinson's disease - Eunju Shin; Joanna Garcia; Christian Winkler; Anders Björklund; Manolo Carta (Neurobiology of Disease, 2012)
Dyskinesia seen in the off-state, referred as graft-induced dyskinesia (GID), has emerged as a serious complication induced by dopamine (DA) cell transplantation in parkinsonian patients. Although the mechanism underlying the appearance of GID is unknown, in a recent clinical study the partial 5-HT1A agonist buspirone was found to markedly reduce GID in three grafted patients, who showed significant serotonin (5-HT) hyperinnervation in the grafted striatum in positron emission tomography scanning (Politis et al., 2010, 2011). Prompted by these findings, this study was performed to investigate the involvement of serotonin neurons in the appearance of GID in the rat 6-hydroxydopamine model.L-DOPA-primed rats received transplants of DA neurons only, DA plus 5-HT neurons or 5-HT neurons only into the lesioned striatum. In DA cell-grafted rats, with or without 5-HT neurons, but not in 5-HT grafts, GID was observed consistently after administration of amphetamine (1.5 mg/kg, i.p.) indicating that grafted DA neurons are required to induce GID. Strikingly, a low dose of buspirone produced a complete suppression of GID. In addition, activation of 5-HT1A and 5-HT1B receptors by 8-OH-DPAT and CP 94253, known to inhibit the activity of 5-HT neurons, significantly reduced GID, whereas induction of neurotransmitter release by fenfluramine administration significantly increased GID, indicating an involvement of the 5-HT system in the modulation of GID. To investigate the involvement of the host 5-HT system in GID, the endogenous 5-HT terminals were removed by intracerebral injection of 5,7-dihydroxytryptamine, but this treatment did not affect GID expression. However, 5-HT terminal destruction suppressed the anti-GID effect of 5-HT1A and 5-HT1B agonists, demonstrating that the 5-HT1 agonist combination exerted its anti-GID effect through the activation of pre-synaptic host-derived receptors. By contrast, removal of the host 5-HT innervation or pre-treatment with a 5-HT1A antagonist did not abolish the anti-GID effect of buspirone, showing that its effect is independent from activation of either pre- or post-synaptic 5-HT1A receptors. Since buspirone is known to also act as a DA D2 receptor antagonist, the selective D2 receptor antagonist eticlopride was administered to test whether blockade of D2 receptors could account for the anti-dyskinetic effect of buspirone. In fact, eticlopride produced complete suppression of GID in grafted animals already at very low dose. Together, these results point to a critical role of both 5-HT1 and D2 receptors in the modulation of GID, and suggest that 5-HT neurons exert a modulatory role in the development of this side effect of neuronal transplantation.